Uma revisão de escopo sobre como as crianças têm percebido e transformado, colaborativamente, espaços públicos - Desirée Rodrigues Ruas (2023)
The participation of children in processes that affect the quality of their lives is a right recognized worldwide. Since the Convention on the Rights of the Child by the United Nations General Assembly (1989), the interest in understanding how the inclusion of children's perspectives in processes of transformation of urban environments has taken place. More recently, this debate gains strength with the struggles for the right to the city as struggles for democracy, inclusion and equity. The present work seeks to understand public spaces according to children's perception and how they have participated in their transformation in the context of Latin America and the Caribbean. For that, a scoping review was carried out in seven electronic databases –– Dialnet, JSTOR, Redalyc, Redib, SciELO, Scopus e Web of Science. Empirical articles published from 1989 to 2022 were included. Complementarily, initiatives that have sought to promote children's participation in decision-making processes were mapped through searches on websites of institutions and public bodies. This review verified a significant growth in the number of studies that aim to understand how children perceive contemporary public spaces and initiatives that aim to involve them in the most varied processes of planning, design and management. On the other hand, the number of studies that seek to evaluate children's participation in these so-called participatory processes is insignificant. The results of this review reinforce the importance of children's criticisms of public spaces being considered in decision-making processes and point to the need for further studies on children's participation in the different initiatives underway in Latin America and the Caribbean. The lack of studies addressing the level of children's participation in decision-making processes is problematic as it prevents feedback between theory-research-practice and, therefore, the fight against forms of pseudo-participation.